Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline 3 Menggunakan Model ADDIE untuk Mendukung Pembelajaran Mendalam di Sekolah Dasar - Nurhalizah; Fadillah Azahra; Ahmad Zainuri; Frika Fatimah Zahra (Yayasan Al-Afif, 2026)
This study discusses the limited availability of interactive media used in elementary schools to promote deep learning. The purpose of this research is to develop interactive learning media using Articulate Storyline 3 based on the ADDIE model. This study employs a development approach, with data collected through observations, interviews, and questionnaires involving teachers and students. The developed media was found to be valid, practical, and effective, as indicated by increased student engagement and understanding during the learning process. The inclusion of interactive components helps enhance meaningful learning experiences and improve students’ enthusiasm. The findings of this study show that technology-based media can support deeper learning in elementary school students. In conclusion, the developed media is suitable for implementation and can improve the quality of learning outcomes.